Design and Development of Procurement Information System for PT Antar Surya jaya - Hadi, Rahman Nur; Sunarto, Dewiyani; Hananto, Valentinus Roby (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Gramedia Printing Group - Surabaya Plant, is a printing and publishing company. One of its main business process is procurement which refer to activity to acquire goods by buying it from supplier. There are some problems found in current process, which are: requester doesn’t know the state of their procurement request which can held down their productivity, logistic give more time and effort to check the procurement request’s approval from central office before purchase the goods, and there’s no managerial level report for decision making. To overcome these problem, a system is required to give requester information about their request, simplify and automate logistic activity, and ability to provide managerial report. Procurement Information System is expected to kept requester informed about their request, to ease logistic in procurement process, and to provide information to be used as source of decision making by managerial level.